Therapeutic Targeting of Signaling Pathways Related to Cancer Stemness - Espinosa-Sánchez, Asunción; Suárez-Martínez, Elisa; Sánchez-Díaz, Laura; Carnero, Amancio (Frontiers in Oncology, 2020)
The theory of cancer stem cells (CSCs) proposes that the different cells within a tumor, as well as metastasis deriving from it, are originated from a single subpopulation of cells with self-renewal and differentiation capacities. These cancer stem cells are supposed to be critical for tumor expansion and metastasis, tumor relapse and resistance to conventional therapies, such as chemo- and radiotherapy. The acquisition of these abilities has been attributed to the activation of alternative pathways, for instance, WNT, NOTCH, SHH, PI3K, Hippo or NF-B pathways, that regulate detoxification mechanisms; increase the metabolic rate; induce resistance to apoptotic, autophagic and senescence pathways; promote the overexpression of drug transporter proteins; and activate specific stem cell transcription factors. The elimination of CSCs is an important goal in cancer therapeutic approaches because it could decrease relapses and metastatic dissemination, which are main causes of mortality in oncology patients. In this work, we discuss the role of these signaling pathways in CSCs along with their therapeutic potential.